SOME EFFECTIVE TEACHING METHODS FOR A1 LEVEL STUDENTS IN ENGLISH CLASSES - Abdujabborova Nazira Ravshanbek kizi; Sh.Nematjonov (Journal of Research in Innovative Teaching and Inclusive Learning, 2023)
This article offers some methods how to plan a good lesson and use interactive techniques to improve A1 level learners’ vocabulary acquisition, comprehension of grammar and tasks during the lesson.